Estimating the Tensile Strength of Ultrahigh-Performance Fiber-Reinforced Concrete Beams - In-Hwan Yang; Changbin Joh; The Quang Bui (Advances in Materials Science and Engineering)
The tensile behavior of ultrahigh-performance fiber-reinforced concrete (UHPFRC) depends on the dispersion and orientation of steel fibers within the concrete matrix. The uneven dispersion of randomly oriented steel fibers in concrete may cause differences in the tensile behavior between material testing specimens and beams. Therefore, in this study, the tensile behavior was investigated by fitting the analysis result of the moment-curvature curve to the experimental result of a UHPFRC beam. To this end, three UHPFRC mixtures with different compressive strengths were fabricated to test the material properties and flexural behavior of UHPFRC beams. Both a single type of steel fiber and a combination of steel fiber types were used with volume fractions of 1.0% and 1.5%, respectively, in the three mixtures. Based on the design recommendations, the material properties of UHPFRC were modeled. The results ultimately show that by fitting the analysis results to the experimental results of the moment-curvature curves, the tensile strength of UHPFRC beams can be reasonably estimated.